(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Questioned documents play a vital role as primary evidence in most cases. Graphology refers to the study of handwriting. Signature refers to the unique characters or symbols written by individuals over time which is impossible to be duplicated by others perfectly. Imitation of others’ signatures is known as signature forgery. Simulated forgery is when a person tries to imitate a signature by seeing the original signature. In this study 450 samples were collected from 45 subjects with every 10 samples of simulated forgery and four individual characteristics namely loop, hook, cusp, and retrace were analyzed using a stereomicroscope. In this study, the result seems that the curved characters are difficult to execute by the subjects whereas the other types of characters were easily executed. This gives a chronological order, in which the individual character such as the hook goes first followed by the cusp, loop, and retrace.